Simulation of multiwavelength conditions in laser picosecond ultrasonics. (July 2021) - Babilotte, Philippe
Complete numerical simulations are given under SciLab ® and MATLAB ® coding environments, concerning propagative acoustic wavefronts, for laser picosecond ultrasonics under multiwavelength conditions. Simulations of the deformation field and its propagation into bulk material are given under different wavelength configurations for optical pump and probe beams, which are used to generate and to detect the acoustic signal. Complete insights concerning the dynamics of the acoustic waves are given, considering the absence of carrier diffusions into the material. Several numerical approaches are proposed concerning both the functions introduced to simulate the wavefront ( Heaviside or error ) and the coding approach (linear/vectorized/ Oriented Object Programming ), under the pure thermo-elastic approach.